Videoscribe as an innovative media for dental health education - Triana Erdiyani; Tedi Purnama; Emini Emini; Vitri Nurilawaty (Center of Excellent (Pusat Unggulan Iptek), 2023)
Background: Along with the development of technology, technology-based educational learning media is also developing, one of the applications that can be used in the development of learning educational videos is the sparkol videoscribe application. Elementary school-age children need appropriate and adequate educational learning media to increase knowledge, especially regarding health, especially dental and oral health, the formation of fun learning situations is also one of the ways to achieve ideal and meaningful learning. The presence of media, especially audio-visual media in learning activities will help foster students' initial interest which is expected to be able to stimulate further curiosity about the material being taught. Purpose: to analyze the effectiveness of videoscribe as a media for dental health education on dental health knowledge in fifth graders of Madrasah Ibtidaiyah Sirojul Banat. Methods: The type of research used in this study was a quasy experiment with a pretest and posttest design with one group design. This research was conducted at Madrasah Ibtidaiyah Sirojul Banat. The sampling technique used total sampling, which amounted to 57 students. Independent variable: videoscribe media and dependent variable: dental health knowledge. Data analysis was tested using paired sample t test. Results: The results of this study show that the average value of dental health knowledge before being educated using videoscribe media is 7.91 and after being given education using videoscribe media is 9.84, with the results of paired sample t-test p<0.001 Conclusion: videoscribe effective as a dental health education media in increasing dental health knowledge.